IMPLICATION OF STORYTELLING THROUGH THE UTILIZATION OF PRIMA LIBRARY SERVICES AS ASPECT OF STRENGTH OF LITERATURE LEARNING FOR CHILDREN'S DEVELOPMENT IN EDUCATIONAL SOCIOLOGY PERSPECTIVE - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2020)
The purpose of the study is to describe; (1). Storytelling implications for child development. The object of research-based discussion is fundamental about content storytelling to foster student interest in reading through the use of library collections. This research focuses on the manifestation of excellent service manifestations because storytelling is also an existing activity and is one form of library service. This research can be called a characteristic historical approach, which is critical research using primary data which is the main information. Collecting data is library research, through the reading activities of various literary literature subjected to, the use of library collections and children's interest in reading, the role of teachers and librarians in children's education. Analysis of research is descriptive qualitative and comes from a variety of reading materials. Content analysis is used to analyze the meaning of storytelling conceptualization, reading interest and the use of library collections. Careful observations are made in the library and classroom, to support constructing the theory. The results of the research implications of storytelling are very influential for children's development.